Uwagi w sprawie niedołężności oraz sposobów ubezpieczenia jej skutków w wybranych krajach Unii Europejskiej - Rubel, Katarzyna (Remarks on infirmity and how to insure its consequences in selected EU countries, 2006)
There are not only various solutions on dependence insurance in different European countries, but also as far as the terminology of the dependence insurance is concerned there have been various tendencies created: the English speaking countries use the definition meaning a long term care is used - long term care, while Germany, and France use the definitions meaning losing independece and autonomy - pflegeversichergung, allocation personnalisee a 1’autonomie. In French speaking countries private insurers also use a term being opposed to independence and autonomy, that is dependence - assurance depandance. It is difficult to speak about Polish definitions, as practically in Poland this risk has been separated neither in social securities system nor by the private insurers, who do not offer such a product yet. On the other hand literature covers the solutions worked out in other countries and definitions usually are some form of translation from other systems. Following the examples of Germany and France, two of the European leading countries in aspect of dependence insurance, one can easily observe the evolution of dependence risk, which started as the diminished element of social security to become a separate, fifth field of social insurances.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 430-437